1999
DOI: 10.3109/13561829909010367
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to full participation by general practitioners in the child protection process: preliminary conclusions from focus group discussions in West Midlands, UK

Abstract: of Birmingham, UK S u m m a r y Focus group discussions were undertaken amongst five primay health care teams in the West Midlands in order to explore and define issues relevant to the participation by general practitioners in the child protection process. It was found thar general practitbners were uncertain of what was prekdy required of them in this respect and that child protection work was a source of significant anxiety for them. It would appear that in many instances, the lead role for child protection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is possible that the responders included GPs with relatively better knowledge and awareness of child protection issues than nonresponders. Taking this potential bias into consideration, it is alarming that the results indicate that GP knowledge of child protection has improved little since Bannon et al's surveys and training needs analysis of GPs in vocational training programmes, which identified unmet child protection training needs (Bannon et al, 1999a(Bannon et al, , 1999bBannon and Carter, 2001). These authors commented that training in child abuse and neglect was not considered to represent a priority in general practice vocational training schemes.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the responders included GPs with relatively better knowledge and awareness of child protection issues than nonresponders. Taking this potential bias into consideration, it is alarming that the results indicate that GP knowledge of child protection has improved little since Bannon et al's surveys and training needs analysis of GPs in vocational training programmes, which identified unmet child protection training needs (Bannon et al, 1999a(Bannon et al, , 1999bBannon and Carter, 2001). These authors commented that training in child abuse and neglect was not considered to represent a priority in general practice vocational training schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Clarity in team roles and expectations has also been suggested as contributing to effectiveness (Bannon, Carter, & Ross, 1999;Hardy & Conway, 1988;Lowe & Herranen, 1978, 1981Mellor & Lindeman, 1998;Miller, Fein, Bishop, & Murray, 1985;Schofield & Amodeo, 1999;Taylor & Tilley, 1990;Temkin-Greener, 1983). Abramson (1990) points out that role competition is an often discussed obstacle to effective teamwork, and suggests that team members may have reduced motivation for team participation because performance evaluation and continuing professional education are located in each profession, rather than within the team.…”
Section: Factors Contributing To Team Effectivenessmentioning
confidence: 99%
“…It has also been shown that nurses and physicians feel unsure when identifying child maltreatment [4][5][6][7][8][9] and feel unsure about the level of evidence required and fear making a report [3,9,10]. Other barriers to reporting have been linked to emotions such as anxiety, uncertainty and stress [4,9,[11][12][13]. A lack of education and training among health care professionals is a repeated concern [3,6,7], and one study [11] found that general practitioners had received little training in child abuse issues compared with social workers.…”
Section: Introductionmentioning
confidence: 99%
“…Other barriers to reporting have been linked to emotions such as anxiety, uncertainty and stress [4,9,[11][12][13]. A lack of education and training among health care professionals is a repeated concern [3,6,7], and one study [11] found that general practitioners had received little training in child abuse issues compared with social workers.…”
Section: Introductionmentioning
confidence: 99%